(untitled) (Research, Society and Development, 2026)
Wheat (Triticum aestivum) is one of the most economically important cereal crops worldwide, being used for both human consumption and animal feed. Owing to the high production costs, its cultivation has become less attractive. The objective of this study was to evaluate the use of broiler poultry litter as a substitute for nitrogen fertilization on wheat yield in a Red Latosol in the state of Paraná, Brazil. The experiment was conducted in Bom Sucesso, Paraná State, Brazil, under the following treatments: T1 – control (no fertilisation); T2 – 2 t ha⁻¹ of poultry litter; T3 – 1 t ha⁻¹ of poultry litter; T4 – 3 t ha⁻¹ of poultry litter; and T5 – 250 kg ha⁻¹ of the 10-15-15 mineral fertiliser. The poultry litter used in this experiment was obtained from the same farm where the trial was established, originating from a broiler production system. Each treatment was applied to a 5 × 5 m plot, with four replicates per treatment arranged in a completely randomised design. Morphological and reproductive variables of wheat were assessed through analysis of variance. Treatment 4 (3 t ha⁻¹ of poultry litter) proved to be a viable alternative to mineral fertilisation (Treatment 5: 250 kg ha⁻¹ of 10-15-15), as it achieved comparable plant morphological characteristics while providing greater economic return to the farmer. It can therefore be concluded that organic fertilisation using poultry litter is an effective strategy for reducing fertiliser-related production costs in wheat cultivation.